(untitled) (gjstudies, 2021)
This research introduces a novel methodological framework that integrates predictive analytics with environmental investment appraisal to address the critical challenge of capitalallocation for sustainability initiatives. Traditional financial models often fail to adequatelycapture the long-term, non-linear, and systemic value of environmental projects, leadingto suboptimal investment decisions and a persistent funding gap for ecological restoration,climate adaptation, and pollution mitigation. Our approach diverges fundamentally fromconventional cost-benefit analysis by employing a hybrid ensemble of machine learning techniques—specifically, a fusion of gradient-boosted regression trees for high-dimensional feature modeling and a recurrent neural network architecture designed to process temporalsequences of ecological and socio-economic data. This model is trained on a unique, multisource dataset comprising historical project outcomes, biophysical sensor data, regulatorytimelines, and community well-being indicators, allowing it to predict not only direct financial returns but also cascading environmental and social value over extended time horizons.A key innovation is the formulation of a ’Resilience Dividend Metric,’ a composite outputthat quantifies the investment’s contribution to systemic ecological stability and adaptive capacity, a dimension largely absent from existing appraisal tools. We validate the frameworkthrough a retrospective case study analysis of wetland restoration projects across threecontinents, demonstrating a significant improvement in predictive accuracy for long-termoutcomes compared to standard net present value calculations. The results indicate thatour model can re-prioritize capital allocation towards projects with higher systemic resilienceyields, even if their short-term financial metrics are less attractive. This work provides afoundational computational tool for investors, governments, and multilateral institutionsseeking to optimize the impact of finite capital in the pursuit of planetary sustainability,representing a substantive cross-disciplinary advance at the intersection of data science,financial engineering, and environmental management.